2019
DOI: 10.1111/nhs.12600
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and its associated factors in incarcerated adults: A cross‐sectional study

Abstract: No evidence exists in the literature concerning the prevalence of insomnia and its associated risk factors among prison inmates in Taiwan. The aim of the present study was to determine the prevalence and factors associated with insomnia among inmates in a large prison in Taiwan. A cross‐sectional anonymous questionnaire survey was conducted at a prison. The participants were 1490 male inmates. Participants completed the self‐reported Insomnia Severity Index–Chinese version questionnaire, and the sociodemograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…The prevalence of insomnia in this sample (45.7%) is high, albeit similar to other findings from a remand prison in Geneva where a rate of 44.3% was reported (Elger, 2004). Among a higher sample (1,490) of incarcerated Taiwanese males in East Asia (Li and Lai, 2019), 26.9% had insomnia. In a further study conducted in India at Guwahati Central Jail, rates of 65% and 72.5% were reported among male and female prisoners, respectively (Raha et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The prevalence of insomnia in this sample (45.7%) is high, albeit similar to other findings from a remand prison in Geneva where a rate of 44.3% was reported (Elger, 2004). Among a higher sample (1,490) of incarcerated Taiwanese males in East Asia (Li and Lai, 2019), 26.9% had insomnia. In a further study conducted in India at Guwahati Central Jail, rates of 65% and 72.5% were reported among male and female prisoners, respectively (Raha et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…Among the incarcerated, the pattern is similar with 44.3% reported in Taiwan (Li and Lai, 2019) and above 60% in India (Raha et al, 2018). Unfortunately, insomnia is mostly undetected, ignored or untreated (Bhaskar et al, 2016), making it a concern for mental health professionals primarily because of its association with aggression (Barker et al, 2016), violence (Gama-Araujo et al, 2020) and suicide (Dewa et al, 2017) in prison settings.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, the prevalence of insomnia and its associated factors are rarely known in steel workers, especially in China. Several socio-demographic, psychological, lifestyle-and be havior-related, as well as occupational factors are associated with insomnia, including anxiety, physical health, religious beliefs [5], sex [6], alcohol consumption [20], a lack of steady income, less frequent social contacts, reduced social capital, living alone [7], shift work [21], occupational stress [8], etc. However, little is known about whether the prevalence of insomnia and its associated factors are different across job categories of steel workers.…”
Section: Questionnaire Measurementsmentioning
confidence: 99%
“…In previous studies [1][2][3][4], the prevalence of insomnia ranged 7.1-79.8% in general populations in the world, e.g., 7.1% in Norway [2], 22.1% in the USA [1], 11.9% in Hong Kong of China [3], and 79.8% in Brazil [4]. In China, studies have shown that the prevalence of insomnia ranges 12.7-55.7% in different populations [5][6][7][8]. Although the prevalence of insomnia varies considerably in terms of criteria and symp-toms, the prevalence above 30% for the global general population is commonly accepted.…”
Section: Introductionmentioning
confidence: 95%